Dementia with Lewy bodies - a disease from the border of Neurology and Psychiatry - case report - Lukasz Kroc; Aleksandra Szczepkowska (Kazimierz Wielki University, 2017)
This article presents the case of 88 years old patient diagnosed and treated for dementia with Lewy bodies.